The efficiency of pistacia atlantica extract as a natural coagulant aid on arsenic removal from aquatic environments - Edris Bazrafshan; Ferdos Kord Mostafapour; Morteza Ahmadabadi; Mojtaba Afsharnia (Gonabad University of Medical Sciences, 2015)
Background: Arsenic has been considered as one of the most hazardous element for the living organisms and its presence in natural waters, can result in serious health and environmental problems. In this study, Pistacia Atlantica seed extract ability in a batch system to remove arsenate from aqueous solutions was investigated. Materials and methods: This study is an experimental study that was performed in a batch reactor. The effects of major operating variables such as coagulant dose (3-35 mg/L), coagulant aid dose (0.5-5 ml/L), initial arsenic (10-1000µg/L), initial turbidity (10 -100 NTU) and pH (2-12) were investigated. Results: The optimum pH for arsenic and turbidity removal by coagulation using ferric chloride was 6. The highest removal for an initial arsenic concentration of 100 µg/L using 5 mg/L ferric chloride and 0.5 ml/L coagulant aid was found to be 94%, while at the same conditions without use of a coagulant aid, required ferric chloride was 10 mg/L. Conclusion: According to achieved results, it was found that Pistacia atlantica seed extract not only was an inexpensive coagulant aid, but also a quite effective factor in removal of As(v) and turbidity from aqueous environments.